“There is a human being there”: A critical pedagogic approach to shift perceptions of patient worthiness in South Africa - Jacobson, Sara Ilyse (Department of Health Sciences Education, 2026)
Socially marginalized individuals in South Africa may be deemed unworthy of scarce resources to promote health and treat illness. Perceptions of patients' relative worthiness impacts health seeking behaviour and outcomes: those deemed unworthy may receive inferior care or be denied health services altogether. Current in-service learning strategies to address unequal treatment in the Primary Health Care facility have not resolved the problem. There is a gap in the literature regarding why perceptions of patient worthiness persist among clinicians in the Global South, and among nurses in particular. This study utilized a critical participatory action research methodology whereby a group of nurses and cross-border migrants - a socially marginalized population in South Africa - engaged in dialogue and critical reflection over a period of one year. Findings indicate that perceptions of worthiness are informed by sociocultural and historic factors that promote the practice of shifting blame for systemic failures onto individuals. Worthiness determinations on the part of clinicians, support staff, and patients from the general population justify dehumanizing actions that harm socially marginalized patients, maintain social and institutional hierarchies, and preserve the unequal status quo. Shifting perceptions of socially marginalized people from stereotypic characters to dynamic individuals is humanizing, and therefore vital to dissuade the practice of triaging patients on the basis of perceived worthiness. Critical reflection on problematic assumptions, motivations, and beliefs through dialogue provides an alternative to traditional in-service training; it holds promise as a strategy to deter worthiness determinations and counter the motive to justify unequal systems. It is essential that facilitators of dialogue-based strategies foster a learning environment in which participants feel free to listen and speak without judgment. Provision of opportunities for learners to consider the perspectives of others through narrative or theatrical activities is equally important, if perceptions of worthiness are to shift.